Short-Term Treatment with the Urease Inhibitor N-(n-Butyl) Thiophosphoric Triamide (NBPT) Alters Urea Assimilation and Modulates Transcriptional Profiles of Genes Involved in Primary and Secondary Metabolism in Maize Seedlings - Zanin, Laura; Venuti, Silvia; Tomasi, Nicola; Zamboni, Anita; De Brito Francisco, Rita M.; Varanini, Zeno; Pinton, Roberto (Frontiers in Plant Science, 2016)
To limit nitrogen (N) losses from the soil, it has been suggested to provide urea to crops in conjunction with the urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT). However, recent studies reported that NBPT affects urea uptake and urease activity in plants. To shed light on these latter aspects, the effects of NBPT were studied analysing transcriptomic and metabolic changes occurring in urea-fed maize seedlings after a short-term exposure to the inhibitor. We provide evidence that NBPT treatment led to a wide reprogramming of plant metabolism. NBPT inhibited the activity of endogenous urease limiting the release and assimilation of ureic-ammonium, with a simultaneous accumulation of urea in plant tissues. Furthermore, NBPT determined changes in the glutamine, glutamate and asparagine contents. Microarray data indicate that NBPT affects ureic-N assimilation and primary metabolism, such as glycolysis, TCA cycle and electron transport chain, while activates the phenylalanine/tyrosine-derivative pathway. Moreover, the expression of genes relating to the transport and complexation of divalent metals was strongly modulated by NBPT. Data here presented suggest that when NBPT is provided in conjunction with urea an imbalance between C and N compounds might occur in plant cells. Under this condition, root cells also seem to activate a response to maintain the homeostasis of some micronutrients.